Urban women: balancing work and childcare - Engle, Patrice L. (International Food Policy Research Institute, 2000)
"As the urban population in all developing regions grows over the next 20 years, governments and families will face unique challenges in their efforts to ensure the well-being of millions of children. They will have to take into account changes in women’s roles, in strategies for childcare, and in the means of obtaining food security. All these changes will have major implications for the livelihoods of people residing in the new urban megacities.... Innovative approaches are needed to provide good childcare, especially for the youngest age group. These approaches must rely on partnerships between employers, workers, and government to provide adequate care. Innovative strategies could include support for parental childcare cooperatives, social insurance to enable mothers or fathers to stay home after the birth of a child, childcare linked to schools, and even the involvement of elders in childcare...." -- from Text